Formation of Logical Thinking in Senior Preschool Children with Severe Speech Disorders from the Standpoint of the L.M. Vekker’s Information Theory of Mental Development - Simanovskij, A.E.; Kornienko, A.O. (Autizm i narušenie razvitiâ, 2024)
Objectives. Contemporary methods of development of logical thinking in preschool children with severe speech disorders (SSD) help to smooth out problems of academic failure at school and social disadaptation. A program for the development of verbal and logical thinking in senior preschool children with SSD was tested. The program was based on the information theory of mental development by L.M. Vekker. Methods. The implementation of the experimental program for the development of logical thinking included the creation of psychological and pedagogical conditions: modeling of surrounding relationships and processes; consistent introduction of models of different levels of concretization of the abstraction; creation of problem situations between surrounding objects and phenomena. The study involved children with a diagnosis of SSD (7 boys, 2 girls) aged 6 to 7 years (M = 6.5), attending a preschool educational organization. To identify "deficits" of verbal-logical thinking in children with speech disorders, a group of children without speech disorders (4 boys, 5 girls) of the same age (M=6.5) was used. Two measurements were taken - before and after the implementation of the formative program. To diagnose the parameters of verbal logical thinking, the "Methodology for studying the level of children's readiness for school" by L.A. Yasyukova was used. Results. Comparison of the indicators of the level of development of thinking in children with speech disorders with the results of children without speech disorders at the first stage of the study showed differences (p≤0.01) in the following parameters: speech and visual classifications, abstract thinking. At the second - developmental - stage, a positive shift at a reliable statistical level occurred in the parameters of the methodology: speech analysis-synthesis (p≤0.05), selection of antonyms (p≤0.05), speech analogies (p≤0.01), speech classifications (p≤0.01), visual analysis synthesis (p≤0.01), visual classifications (p≤0.01). Conclusions. The results of the study showed that children with speech disorders have learned to use symbolic and speech models to understand logical relationships at the level of visual-effective and visual-figurative thinking. According to the indicator visual analysis-synthesis, children with speech disorders demonstrated results even higher than children without speech disorders. Work is planned to further replenish the children's vocabulary, to include in the program a set of training in different types of judgments and conclusions. Актуальность и цель. Современные методы развития логического мышления у детей дошкольного возраста с тя желыми нарушениями речи (ТНР) позволяют сгладить проблемы неуспеваемости в школе и трудности социаль ной адаптации. Проведена апробация авторской программы по формированию словесно-логического мышления у старших дошкольников с ТНР. Программа основана на информационной теории развития психики Л.М. Веккера. Методы и методики. Реализация экспериментальной программы формирования логического мышления включала создание психолого-педагогических условий: моделирования окружающих отношений и процес сов; последовательного введения моделей разного уровня абстракции; создания проблемных ситуаций между окружающими объектами и явлениями. В исследовании участвовали дети с диагнозом ТНР (7 мальчиков, 2 девочки) в возрасте от 6-ти до 7-ми лет (M=6,5), посещающие дошкольную образовательную организацию. Для выявления дефицитов словесно-логического мышления у детей с нарушениями речи сформирована груп па детей без нарушений речи (4 мальчика, 5 девочек) того же возраста (M=6,5). Проведены два замера - до и после реализации формирующей программы. Для диагностики параметров словесно-логического мышления использовалась Методика исследования уровня готовности детей к обучению в школе Л.А. Ясюковой. Результаты. Сравнение показателей уровня развития мышления у детей с ТНР с результатами детей без на рушений речи на первом этапе исследования показало достоверные различия (p≤0.01) по следующим параме трам: речевые и визуальные классификации, абстрактное мышление. На втором, развивающем, этапе позитив ный сдвиг на достоверном статистическом уровне произошел по параметрам: речевой анализ-синтез (p≤0.05), подбор антонимов (p≤0.05), речевые аналогии (p≤0.01), речевые классификации (p≤0.01), визуальный анализ синтез (p≤0.01), визуальные классификации (p≤0.01). Выводы. Результаты исследования показали, что дети с ТНР научились использовать знаковые и речевые модели для понимания логических отношений на уровне наглядно-действенного и наглядно-образного мыш ления. По показателю визуальный анализ-синтез дети с ТНР продемонстрировали результаты даже более вы сокие, чем дети без речевых нарушений. Планируется работа по дальнейшему пополнению речевого запаса детей, по включению в программу блока обучения разным типам суждений и умозаключений.